2020
DOI: 10.9778/cmajo.20190226
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and outcomes of diabetes in Ontario First Nations children: a longitudinal population-based cohort study

Abstract: he prevalence of type 2 diabetes in children is increasing worldwide. 1-3 In 2006-2008, the incidence of childhood-onset type 2 diabetes in Canada was estimated at 1.54 per 100 000 per year, with the highest incidence in Manitoba (12.45 per 100 000 per year); in Ontario, the incidence was 1.7 per 100 000 per year. 4 First Nations children in Canada have the highest incidence of type 2 diabetes, at 23.2 per 100 000 per year. 4 In Manitoba and northwestern Ontario, 87% of children with type 2 diabetes have First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…The type 2 diabetes prevalence in the latter study was highest in the oldest age group (12-17 years), among Black participants, and among female participants, which mirrors the findings from the current study. A Canadian study reported an increase in the prevalence of type 2 diabetes among First Nations youths younger than 20 years from 1.7 per 1000 youths in 1995 to 5.7 per 1000 youths in 2015, an absolute increase of 4.0 per 1000 youths, or 235%, over 20 years . In these 3 studies, the type 2 diabetes prevalence estimates were higher than the current study, but the prevalence approximately doubled over the observation period in each study.…”
Section: Discussioncontrasting
confidence: 83%
“…The type 2 diabetes prevalence in the latter study was highest in the oldest age group (12-17 years), among Black participants, and among female participants, which mirrors the findings from the current study. A Canadian study reported an increase in the prevalence of type 2 diabetes among First Nations youths younger than 20 years from 1.7 per 1000 youths in 1995 to 5.7 per 1000 youths in 2015, an absolute increase of 4.0 per 1000 youths, or 235%, over 20 years . In these 3 studies, the type 2 diabetes prevalence estimates were higher than the current study, but the prevalence approximately doubled over the observation period in each study.…”
Section: Discussioncontrasting
confidence: 83%
“…Once a rare disease in youth, T2D is becoming more common and accounts for a significant proportion of youth onset diabetes in certain at‐risk populations. Worldwide incidence and prevalence of T2D in children and adolescents vary substantially among countries, age categories and ethnic groups 129–134 . The incidence and prevalence of T2D are highest among youth from a minority race/ethnicity, 99 likely because of many factors, including genetics, metabolic characteristics, cultural/environmental influences, and quality of and access to health care 135,136 …”
Section: Epidemiology Of T2dmentioning
confidence: 99%
“…Thus, reducing the duration and number of hospitalizations will be effective in reducing the cost of treatment of DFU. Patients with DFU may need to stay in the hospital for a longer duration due to uncontrolled hyperglycemia, long-term wound care, late-healing wound infections, debridement, amputations, and emerging complications; (12) these factors contributed to increasing the cost. The average cost was also found to increase as the Wagner grade increased.…”
Section: Discussionmentioning
confidence: 99%